Power consumption in spatial cognition. Issue 7 (23rd October 2013) - Odeh, Maha; Zorba, Nizar; Verikoukis, Christos; Bader, Faouzi; Demestricas, Panagiotis; DaSilva, Luiz; Harada, Hiroshi
ABSTRACT Multiple input multiple output adds a new dimension to be exploited in cognitive radio by simultaneously serving several users. The spatial domain that is added through multiple input multiple output is another system resource that has to be optimised and shared when possible. In this paper, we present a spatial sharing that is carried out through zero‐forcing beamforming. Power consumption in such a scenario is discussed and compared with single‐user case to evaluate the feasibility of employing spatial cognition from the power perspective. Closed‐form expressions are derived for the consumed power and data rate at different transmission schemes. Finally, a joint power rate metric is deduced to provide a comprehensive measure of the expediency of spatial cognitive scenario. Copyright © 2013 John Wiley & Sons, Ltd.